$5 × 5$ -graded Lie algebras, cubic norm structures and quadrangular algebras - Tom De Medts; Jeroen Meulewaeter (Forum of Mathematics, Sigma)
We study simple Lie algebras generated by extremal elements, over arbitrary fields of arbitrary characteristic. We show the following: (1) If the extremal geometry contains lines, then the Lie algebra admits a